Hypoxic Preconditioning Protects SH-SY5Y Cell against Oxidative Stress through Activation of Autophagy. Issue 12 (December 2018) - Tan, Xiaomu; Azad, Sherwin; Ji, Xunming
Oxidative stress plays a role in many neurological diseases. Hypoxic preconditioning (HPC) has been proposed as an intervention that protects neurons from damage by altering their response to oxidative stress. The aim of this study was to investigate the mechanisms by which HPC results in neuroprotection in cultured SH-SY5Y cells subjected to oxidative stress to provide a guide for future investigation and targeted interventions. SH-SY5Y cells were subjected to HPC protocols or control conditions. Oxidative stress was induced by H2 O2 . Cell viability was determined via adenosine triphosphate assay. Rapamycin and 3-methyxanthine (3-MA) were used to induce and inhibit autophagy, respectively. Monodansylcadaverine staining was used to observe the formation of autophagosomes. Levels of Microtubule-associated protein light chain 3 B (LC3B), Beclin 1, and p53 were measured by Western blot. Reactive oxygen species (ROS) were also determined. Cell viability in the HPC group following 24-h exposure to 600 μM H2 O2 was 65.04 ± 12.91% versus 33.14 ± 5.55% in the control group. LC3B, Beclin 1, and autophagosomes were increased in the HPC group compared with controls. Rapamycin mimicked the protection and 3-MA decreased the protection. There was a moderate increase in ROS after HPC, but rapamycin can abolish the increase and 3-MA can enhance the increase. p53 accumulated in a manner consistent with cell death, and HPC-treated cells showed reduced accumulation of p53 as compared with controls. Treatment with rapamycin decreased p53 accumulation, and 3-MA inhibited the decrease in p53 induced by HPC. HPC protects against oxidative stress in SH-SY5Y cells. Mechanisms of protection may involve the activation of autophagy induced by ROS generated from HPC and the following decline in p53 level caused by activated autophagy in oxidative stress state. This is in line with recent findings in nonneuronal cell populations and may represent an important advance in understanding how HPC protects neurons from oxidative stress.